The Impact of Gastric Bypass on Gastroesophageal Reflux Disease in Morbidly Obese Patients. Issue 1 (January 2016) - Madalosso, Carlos Augusto S.; Gurski, Richard Ricachenevsky; Callegari-Jacques, Sidia M.; Navarini, Daniel; Mazzini, Guilherme; Pereira, Marina da Silva
Abstract : Objective: To assess the impact of Roux-en-Y gastric bypass (GBP) on gastroesophageal reflux disease (GERD) in morbidly obese patients. Background: Recently, authors have reported that early results of GBP can control GERD. However, longer follow-ups based on objective parameters for GERD are missing. Methods: Fifty-three patients [15 men (28%), 39 years old (range, 18–59), body mass index = 46 ± 7.7 kg/m 2 ] were consecutively evaluated for GERD irrespectively of related symptoms, before the operation (E1) and at 6 (E2) and 39 ± 7 months postoperatively (E3). The end points were (1) esophageal syndromes based on the Montreal Consensus and (2) an esophageal acid exposure assessment. Results: Body mass index dropped from 46 ± 7.7 kg/m 2 at E1 to 30 ± 5.2 kg/m 2 at E3. Typical reflux syndrome displayed a significant decrease from 31 (58%) at E1 to 8 (15%) at E2 and 5 (9%) at E3. Statistically significant differences occurred between E1 and both postoperative evaluations ( P < 0.001). Reflux esophagitis was detected in 24 (45%), 17 (32%), and 10 patients (19%) at E1, E2, and E3, respectively ( P = 0.002). The incidence of GERD decreased in 34 (64%) and 21 (40%) patients at E1 and E2, respectively, and then in 12 (23%) patients at E3. DeMeester scores reduced from 28.6 (E1) to 9.4 (E2) and 1.2 (E3) ( P < 0.001). Conclusions: For most morbidly obese patients, in addition to causing significant weight loss, GBP reduces GERD symptoms, improves reflux esophagitis, and decreases esophageal acid exposure for longer than 3 years.